Constitucionalismo latino-americano: proteção jurídica da biodiversidade e dos conhecimentos tradicionais associados dos povos indígenas no município de São Gabriel da Cachoeira - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The pan-Amazon countries are characterized by their megadiversity in numerous aspects, from their ethnic-racial formation, in the encounter of races, to the formation of National States based on Eurocentric and anthropocentric influence. Such subjugation was decisive for the aspirations of the colonialist countries, but above all in the perpetuation of the submission of the peoples of the global south, giving rise to coloniality. In turn, this same coloniality gave rise to the Andean peoples, especially Ecuador and Bolivia, a feeling of decolonial belonging, through the cosmovision of the original peoples, worshiping values, traditions and way of life, such as the "buen vivir", “suma qamaña”, “sumak kawsai” and “teko porã”, translated in the new Latin American Constitutionalism. Thus, the legal protection of traditional knowledge associated with biodiversity under this approach is essential for the recognition of the right of ancestral peoples to live under their own vision of the world and that they are guaranteed fair and equitable sharing for the use of their associated traditional knowledge according to the objectives of the Convention on Biological Diversity, the Nagoya Protocol, Law no 13.123, of May 20, 2015 and its regulations. Thus, it is intended to analyze the aforementioned tutelage in the context of the municipality of São Gabriel da Cachoeira due to its expressive presence of indigenous peoples and the Amazon biome, through an exploratory bibliographical and jurisprudential research, through books, sentences, magazines and articles related to the subject studied here, using the theoretical-methodological instruments of historical-dialectical materialism from a qualitative approach, with a view to proposing legislative changes and/or legal norms and public policies that enable the effective protection of associated traditional knowledge to the biodiversity of indigenous peoples.
Latin american constitutionalism: legal protection of biodiversity and associated traditional knowledge of indigenous peoples in the municipality of São Gabriel da Cachoeira
Keywords: Indígenas - São Gabriel da Cachoeira (AM); Conhecimento tradicional associado - São Gabriel da Cachoeira (AM); CIENCIAS SOCIAIS APLICADAS; Constitucionalismo latino-americano; Povos originários; São Gabriel da Cachoeira; Biodiversidade; Conhecimento tradicional associado